A comprehensive sensitivity study of major passive design parameters for the public rental housing development in Hong Kong. (15th December 2015) - Chen, Xi; Yang, Hongxing; Zhang, Weilong
Abstract: This paper presents a comprehensive SA (sensitivity analysis) of the typical PRH (public rental housing) development in Hong Kong based on a combined building energy, daylight and AFN (airflow network) simulation. A generic building model is constructed with a proposed MM (mixed-mode) ventilation control strategy to fulfill the thermal comfort requirement in the local green building guidance. The numerical modeling results are used to conduct both local and global sensitivity analyses to determine the relative importance of major passive design parameters, which comprehensively cover design aspects of the building layout, envelop thermophysics, building geometry and infiltration & air-tightness. The calculated global and local sensitivity indices on the cooling energy prove that the window solar heat gain coefficient, window to ground ratio, external obstruction and overhang projection fraction are the four most influential passive design factors. Similar results are also obtained when the lighting energy is specified as the output of the sensitivity analysis. The optimized building model derived from the sensitivity analysis is anticipated to achieve an energy saving of 41.6% compared to the baseline model as stipulated by the local building regulation. It is believed that sensitivity analysis is useful for identifying crucial design parameters to facilitate further optimization of the building performance in early architectural design stages. Highlights: A high-rise residential building with passive design strategies is studied. A combined building energy, daylight and airflow network simulation is conducted. Local and global sensitivity analyses are adopted to assess selected design factors. Sensitivity indices indicates window features as most influential factors. Optimized building model is anticipated to achieve an energy saving of 41.6%.